Peningkatan Kapasitas Terapi Berhenti Merokok Bagi Tenaga Kesehatan Melalui Hypnoteraphy di Puskesmas - Sabit - Tohari; Laelatul Anisah (Universitas Muria Kudus, 2019)
The benefits of this activity are (1) training medical personnel in overcoming smoking cessation, (2) increasing the potential that exists in medical personnel. The subjects in this activity were medical staff at the Pukesmas and volunteers stopped smoking. The results of this activity are orphanage students improve communication, deepen the potential within themselves and be able to make decisions according to their abilities. In this activity received a positive response from the participants. Not only is the occurrence of public trust regarding the counseling profession.